PENERAPAN PERANGKAT PEMBELAJARAN BERBASIS PROYEK MATA DIKLAT SISTEM OPERASI JURUSAN TKJ - Risma Wiwita (STKIP Pesisir Selatan, 2019)
This development research aims to development of Project Based Learning on System Operation at computer and networking technic this research methods IDI development research, such as the prosedure of IDI development is: define, develop and evaluate. Types of data is primary data where the data provided by the experts, teachers and students, An analysis of the data used are technical data descriptive analysis was to describe validity, practicality, effectiveness and creative of products using Learning. Based on the data analysis that was did to research methods IDI development research. The results obtained from this research and development in the book teacher and book students after validity as follows: (1) The validity of the Project Based Learning declared valid, (2) The practicalities of Project Based Learning based on teachers after validity revealed practically, (3) Effectiveness of Project Based Learning effective in improving students learning outcomes before with after using Project Based Learning, (4) The creative of Project Based Learning, Based on the findings of this study was concluded that this Project Based Learning was valid, practical effective and creative to be used asa medium of learning was in the system operation